Understanding students' active reading in phygital learning environments: a study of smartphone-based textbook companions in Indian classrooms - Prajapati, Sunny Prakash; Das, Syaamantak (Frontiers in Education, 2025)
IntroductionActive reading is essential for students' comprehension and engagement when working with complex academic texts. Although digital textbooks and multimedia resources are increasingly combined with print materials, little is known about how students engage in cross-media active reading using smartphone-based companion applications in authentic learning contexts.MethodsWe conducted a two-part investigation with high school students in India. First, an exploratory survey of 45 students examined their reading preferences and use of supplemental resources. Second, a mixed-methods study with 26 students compared active reading behaviors across two systems: a printed textbook with a smartphone companion app, and an interactive digital textbook. Data sources included video recordings of the reading process, validated self-report instruments for cognitive load and engagement, and students' textual responses to task questions.ResultThe result showed that the phygital system (printed textbook + companion app) was associated with lower cognitive load, higher engagement, and linguistically richer written responses compared to the digital textbook system.DiscussionThese findings suggest that phygital learning environments can enhance academic reading experiences and inform the design of technology-integrated instructional materials.